Nijmegen breakage syndrome - NBS: а rare clinical case in Kazakhstan - Elena F. Kovzel; Bayan Gani; Adil A. Zhamankulov; Assel K. Baigojayeva (National Scientific Medical Center, 2024)
Nijmegen syndrome is a primary immunodeficiency characterized by chromosomal instability, microcephaly, physical retardation, specific disorders of the facial skeleton, as well as a predisposition to cancer. Most patients of Slavic origin have a homozygous mutation with the del5 founder effect in the NBS gene. The frequency of occurrence is 1:100000population. The highest frequency of carriage in the population of the del5 mutation in the NBS gene in the Czech Republic is 1:154, in Ukraine - 1:182, in Poland - 1:190. This pathology is presented in our clinical practice for the first time, and therefore we would like to provide data for a wide review